Sondertrassenzuschläge und Co. zulässig? Die Schranken der Infrastrukturentgelte. - Uhlenhut, Bernd H. (Deutscher Verkehrs-Verl., 2007)
Neben den Bedingungen des Infrastrukturzugangs und der Infrastrukturnutzung sind die Kosten der Erbringung von Eisenbahnverkehrsleistungen von grundlegender Bedeutung. Sie sind für die Kalkulation des Eisenbahnverkehrsunternehmens (EVU) und seine Position im Wettbewerb entscheidend. Auf Grund der Wettbewerbsrelevanz unterschiedlicher Entgelte ist dabei die Erhebung gesonderter Zuschläge bzw. die Einräumung von Rabatten besonders brisant. difu

Questions regarding the level of user charges continue to be raised in connection with the use of railway infrastructure installations. Conflicts arising out of this frequently need to be resolved in court. Limits to user charges are stipulated in the laws applicable to railways and cartels as well as in civil laws. It is prohibited to treat users of railway infrastructure installations in any way differently. In addition, the level of user charges is fixed within the parameters of the railway law yet some questions do remain unanswered. There are specific and rather limiting rules for applying extra charges and for granting discounts. Not admissible is the levy of additional charges for the use of 'special purpose' or new rail tracks. A reduction of user charges is usually not justifiable since there is no evidence of cost savings. difu
Keywords: Öffentlicher Verkehr; Verkehrsunternehmen; Eisenbahn; Schienenpersonenverkehr; Nahverkehr; Gebühr; Verkehrsinfrastruktur; Finanzierung; Wettbewerb; Infrastrukturzugang; Eisenbahnrecht; Infrastrukturnutzung; Entgelt; Verkehrsleistung